2011
DOI: 10.1179/1743289810y.0000000019
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterisation of nanocellulose reinforced polyamide-6

Abstract: A procedure is described for preparing polyamide-6 (PA-6) reinforced with cellulose nanofibres. The cellulose nanofibres were obtained from flax and microcrystalline cellulose (MCC) using combinations of acid hydrolysis, ball milling and ultrasound, then characterised by transmission electron microscopy (TEM) in order to determine their size and geometry. The nanofibres produced from the different feedstock sources were of a similar order with lengths ranging from 21 to 300 nm and diameters between 2 and 22 nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 28 publications
3
28
0
4
Order By: Relevance
“…These findings are in excellent accordance with the reported literature (Qua et al 2011). The yielded nanocellulose produced in this study showed a finer fibrillar structure and reduced fiber diameter compared with native cellulose (23.1 ± 11.5 μm).…”
Section: Surface Characterization Analysis (Fe-sem)supporting
confidence: 82%
See 2 more Smart Citations
“…These findings are in excellent accordance with the reported literature (Qua et al 2011). The yielded nanocellulose produced in this study showed a finer fibrillar structure and reduced fiber diameter compared with native cellulose (23.1 ± 11.5 μm).…”
Section: Surface Characterization Analysis (Fe-sem)supporting
confidence: 82%
“…In this study, the size distribution of all two types of nanocellulose (20 to 80 nm) was thus rather similar and relatively close to that reported for waste sackcloth (20 to 50 nm; Cao et al 2015), borer powder (20 to 70 nm; Hu et al 2014), rubberwood (10 to 90 nm; Jonoobi et al 2011), sugarcane bagasse (20 to 60 nm; Kumar et al 2014), flax (2 to 50 nm; Qua et al 2011), and old corrugated container (15 to 80 nm; . …”
Section: Morphological Analysis (Tem)supporting
confidence: 51%
See 1 more Smart Citation
“…Its properties depend on the polyether/polyamide ratio (Fakirov 2005;. Qua and Hornsby (2011) worked on reinforcing Polyamid-6 by nanocellulose, but there is no report about preparing a nanocomposite by Pebax reinforced with nanocellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Em paralelo a esse cenário, pesquisadores têm focado seus trabalhos no processamento de nanocompósitos, devido aos fortes efeitos de reforço a uma fração de volume baixo [5][6][7][8][9]. Na nanoescala surgem novos fenômenos que não aparecem na macroescala.…”
unclassified